Validity of radiographic assessment of the knee joint space using automatic image analysis. Issue 5 (2nd September 2016) - Komatsu, Daigo; Hasegawa, Yukiharu; Kojima, Toshihisa; Seki, Taisuke; Ikeuchi, Kazuma; Takegami, Yasuhiko; Amano, Takafumi; Higuchi, Yoshitoshi; Kasai, Takehiro; Ishiguro, Naoki
Abstract: Objectives : The present study investigated whether there were differences between automatic and manual measurements of the minimum joint space width (mJSW) on knee radiographs. Methods : Knee radiographs of 324 participants in a systematic health screening were analyzed using the following three methods: manual measurement of film-based radiographs (Manual), manual measurement of digitized radiographs (Digital), and automatic measurement of digitized radiographs (Auto). The mean mJSWs on the medial and lateral sides of the knees were determined using each method, and measurement reliability was evaluated using intra-class correlation coefficients. Measurement errors were compared between normal knees and knees with radiographic osteoarthritis. Results : All three methods demonstrated good reliability, although the reliability was slightly lower with the Manual method than with the other methods. On the medial and lateral sides of the knees, the mJSWs were the largest in the Manual method and the smallest in the Auto method. The measurement errors of each method were significantly larger for normal knees than for radiographic osteoarthritis knees. Conclusions : The mJSW measurements are more accurate and reliable with the Auto method than with the Manual or Digital method, especially for normal knees. Therefore, the Auto method is ideal for the assessment of the knee joint space.